Deep Eutectic Solvents‐Based Ionogels with Ultrafast Gelation and High Adhesion in Harsh Environments. (14th February 2023) - Ge, Gang; Mandal, Kalpana; Haghniaz, Reihaneh; Li, Mengchen; Xiao, Xiao; Carlson, Larry; Jucaud, Vadim; Dokmeci, Mehmet Remzi; Ho, Ghim Wei; Khademhosseini, Ali
Abstract: Adhesive materials have recently drawn intensive attention due to their excellent sealing ability, stimulating advances in materials science and industrial usage. However, reported adhesives usually exhibit weak adhesion strength, require high pressure for strong bonding, and display severe adhesion deterioration in various harsh environments. In this study, instead of water or organic solvents, a deep eutectic solvent (DES) is used as the medium for the photopolymerization of zwitterionic and polarized monomers, thus generating a novel ionogel with tunable mechanical properties. Multiple hydrogen bonds and electrostatic interactions between DES and monomers facilitated ultrafast gelation and instant bonding without any external pressure, which has rarely been reported previously. Furthermore, high adhesion in different harsh environments (e.g., water, acidic and basic buffers, and saline solutions) and onto hydrophilic (e.g., glass and tissues) and hydrophobic (e.g., polymethyl methacrylate, polystyrene, and polypropylene) adherends is demonstrated. Also, the high stretchability of the ionogel at extreme temperatures (−80 and 80 °C) indicates its widespread applications. Furthermore, the biocompatible ionogel shows high burst pressure onto stomach and intestine tissues to prevent liquid leakage, highlighting its potential as an adhesive patch. This ionogel provides unprecedented opportunities in the packaging industry, marine engineering, medical adhesives, and electronic assembly. Abstract : By utilizing deep eutectic solvents as a green media for the photopolymerization of zwitterionic and polarized monomers, a novel ionogel with the capacities of ultrafast gelation and instant bonding is proposed. Strong adhesion in harsh environments (e.g., underwater, acidic and basic buffers, and saline solutions), ductile stretchability, high biocompatibility, and desirable burst pressure highlight the ionogel's widespread applications.